Comparison of Four Adsorption Equations Used for the Description of the Systems: Porous Solid/Binary Liquid Non-Electrolyte Solution - D. Ziólkowska (Adsorption Science & Technology, 1999)
The solution analogues of four single gas adsorption equations have been examined. The derived expressions have been applied to the description of the experimental adsorption isotherms on to microporous active carbons from binary liquid solutions with limited component miscibility. Statistical analyses of the individual adsorption equations, as well as comparisons of the optimized results obtained from different adsorption equations, have been undertaken.